(untitled) (Fiep Bulletin - online, 2013)
The aim of this study was to analyze whether the workplace contributes to thethe stress of pré-vestibulandos, and if there is improvement in the performance of studies and in the quality of life for middle school students. Participated in this study 61 students of both sexes, from a private school teaching, with an average age of 21 ± 5 years. Through the individual questionnaire, buscou-se avaliar a prática de atividade física e o nível de est We sought to evaluate the practice of physical activity and the stress level of students. The young participants of this survey indicated a high percentage with respect to physical inactivity, anxiety and sleep disorder, and an improvement in mood and concentration for the classes. The stage of adolescence is a period very susceptible to stress and that young people are exposed to a variety of transformations in a short space of time, which requires constant adjustments, thus making the phenomenon of a constant stress. Is of paramount importance to realization of physical activity among students of 3° year of high school, because they are going through the phase of career choices But the gymnastics comes as an option for physical activity for the young students who don’t have the time to perform the same.